1999
DOI: 10.1177/135910539900400406
|View full text |Cite
|
Sign up to set email alerts
|

The Theory of Planned Behaviour as Predictor of Exercise

Abstract: In a test of the predictive utility of the theory of planned behaviour alone and in conjunction with a number of additional variables, 114 participants completed questionnaires measuring predictor variables and, three weeks later, reported exercise. The results of the present study provide partial support for the theory. Past behaviour was the most predictive variable. Subjective norm was not a significant predictor of intention to exercise. Attitude towards exercise was also not a predictor of exercise intent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
43
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(52 citation statements)
references
References 39 publications
5
43
0
1
Order By: Relevance
“…For example, many studies using the TPB reported no role for subjective norms (eg. Bozionelos & Bennett, 1999;Jamner, Wolitski, Corby & Fishbein, 1998;De Wit, Stroebe, De Vroome, Sandfort & Van Griensen, 2000), some showed no predictive role for perceived behavioural control (eg. Flynn et al, 1997;Sutton, McVey & Glanz, 1999) and some showed no role for attitudes (eg.…”
Section: Can the Theory Be Tested?mentioning
confidence: 99%
“…For example, many studies using the TPB reported no role for subjective norms (eg. Bozionelos & Bennett, 1999;Jamner, Wolitski, Corby & Fishbein, 1998;De Wit, Stroebe, De Vroome, Sandfort & Van Griensen, 2000), some showed no predictive role for perceived behavioural control (eg. Flynn et al, 1997;Sutton, McVey & Glanz, 1999) and some showed no role for attitudes (eg.…”
Section: Can the Theory Be Tested?mentioning
confidence: 99%
“…Based on Social cognitive theory (SCT)'s variables (Blaney et al, 2010;Rogers et al, 2011), we retained experienced fatigue, experienced side-effects (hair loss, scars), depression, and lack of information. Four cancer-related barriers items were then formulated, for instance: I am too tired to practice regular PA, which represents consequences of treatment that prevents exercising regularly (Bozionelos & Bennett, 1999). We decided to incorporate the guidelines on moderate-intensity PA only because if a barrier appears in moderate-intensity PA, it will remain present in vigorous-intensity PA and in order to avoid discouragement in a sample of inactive or sedentary women.…”
Section: Study 1 Methodsmentioning
confidence: 99%
“…In this perspective, the most distinctive determinant related to adoption of health behavior is reported to be perceived barriers (Rogers et al, 2007(Rogers et al, , 2011Bozionelos & Bennett, 1999;Courneya & Friedenreich, 1999). Barriers generally reported in this vein by cancer survivors, like experienced nausea, fatigue, lack of energy, and pain, contribute to directly hinder in taking up PA as a routine (Blaney et al, 2010;Courneya & Friedenreich, 1999;Lewis & Lynch, 1993).…”
Section: La Identificación De Barreras Como Intervención Para Involucmentioning
confidence: 99%
See 2 more Smart Citations